2023
DOI: 10.3390/horticulturae9060629
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Different Extraction Techniques for Separation of Artemisinin from Sweet Wormwood (Artemisia annua L.)

Abstract: Sweet wormwood (Artemisia annua L.) valorization is gaining importance due to the presence of the health-promoting bioactive compound, artemisinin. Considering the wide possible application of artemisinin drug formulations, new, greener technologies in their production are welcome. In this study, artemisinin was extracted from A. annua leaves using green extraction technologies (ultrasound-assisted extraction, supercritical CO2 extraction, deep eutectic solvent extraction and subcritical water extraction) in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In addition, wormwood can treat serious gastrointestinal diseases caused by parasites such as pinworms, roundworms, and tapeworms. From a historical perspective, wormwood was once considered the preferred drug for treating intestinal worms, but due to the serious side effects associated with absinthe, it is no longer popular [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In a 2017 research report, extracts of Artemisia absinthium were found to be effective in killing Hymenolepis nana in laboratory mice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, wormwood can treat serious gastrointestinal diseases caused by parasites such as pinworms, roundworms, and tapeworms. From a historical perspective, wormwood was once considered the preferred drug for treating intestinal worms, but due to the serious side effects associated with absinthe, it is no longer popular [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In a 2017 research report, extracts of Artemisia absinthium were found to be effective in killing Hymenolepis nana in laboratory mice.…”
Section: Introductionmentioning
confidence: 99%
“…The available research data indicate that the biologically active potential of the various Artemisia species is far from being fully studied, and their conventional applications do not utilize their properties fully. Therefore, the current investigations [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] of the chemical compositions and biological activity of the various Artemisia L. species hold particular significance and are experiencing a real surge as they are presently in the focus of bioorganic and bioanalytical chemistry. The chromatography–mass spectrometry technique is widely acknowledged as the most-appropriate and -informative approach for the analysis of extracts or essential oils, specifically their chemical compositions, due to its ability to combine high separation power with reliable mass spectrometry detection [ 56 ].…”
Section: Introductionmentioning
confidence: 99%